Kemampuan Ekstrak Daun Beluntas (Pluchea Indica Linn) Sebagai Larvasida Alami Terhadap Jentik Aedes aegypti - Anggie aulia Idris; Muhammad Khidri Alwi; Hidayat (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes and remains a public health problem in various endemic areas. Vector control is an important strategy in preventing DHF, including through the use of botanical larvicides that are more environmentally friendly than chemical larvicides. This study aims to determine the effectiveness of beluntas leaf extract (Pluchea indica Linn.) in killing Aedes aegypti larvae. This study is a quasi-experimental study with three variations in beluntas leaf extract concentration, namely 10%, 20%, and 30%. Each treatment was repeated three times, with 20 Aedes aegypti larvae per replication. Observations were made every hour for 24 hours to determine the number of larvae deaths. The results showed that Beluntas leaf extract at 10% concentration caused 80% larval mortality within 5 hours. At a concentration of 20%, larval mortality reached 80% within 3 hours, while a concentration of 30% was able to cause larval mortality of 85% within 1 hour. These results indicate that the higher the concentration of the extract used, the faster and greater the level of larval mortality. It can be concluded that the extract of beluntas leaves (Pluchea indica Linn.) is effective as a botanical larvicide against Aedes aegypti larvae, with a concentration of 30% showing the highest effectiveness. Beluntas leaf extract has the potential to be developed as an environmentally friendly, relatively safe alternative for controlling dengue vectors.